Ti Porous Film-Supported NiCo2S4 Nanotubes Counter Electrode for Quantum-Dot-Sensitized Solar Cells - Jianping Deng; Minqiang Wang; Xiaohui Song; Zhi Yang; Zhaolin Yuan (Nanomaterials, 2018)
In this paper, a novel Ti porous film-supported NiCo2S4 nanotube was fabricated by the acid etching and two-step hydrothermal method and then used as a counter electrode in a CdS/CdSe quantum-dot-sensitized solar cell. Measurements of the cyclic voltammetry, Tafel polarization curves, and electrochemical impedance spectroscopy of the symmetric cells revealed that compared with the conventional FTO (fluorine doped tin oxide)/Pt counter electrode, Ti porous film-supported NiCo2S4 nanotubes counter electrode exhibited greater electrocatalytic activity toward polysulfide electrolyte and lower charge-transfer resistance at the interface between electrolyte and counter electrode, which remarkably improved the fill factor, short-circuit current density, and power conversion efficiency of the quantum-dot-sensitized solar cell. Under illumination of one sun (100 mW/cm2), the quantum-dot-sensitized solar cell based on Ti porous film-supported NiCo2S4 nanotubes counter electrode achieved a power conversion efficiency of 3.14%, which is superior to the cell based on FTO/Pt counter electrode (1.3%).